Cortical response of the ventral attention network to unattended angry facial expressions: an EEG source analysis study - Inuggi, Alberto; Sassi, Federica; Castillo, Alejandro; Campoy, Guillermo; Leocani, Letizia; García Santos, José M.; Fuentes, Luis J. (Frontiers in Psychology, 2014)
Introduction: We used an affective prime task composed of emotional (happy, angry, and neutral) prime faces and target words with either positive or negative valence. By asking subjects to attend to either the faces’ emotional expression or to the glasses’ shape, we assessed whether angry facial expressions were processed when they were unattended and task-irrelevant. Methods: We conducted a distributed source analysis on the corresponding event-related potentials focused on the early activity of face processing and attention networks’ related areas. We also evaluated the magnitude of the affective priming effect. Results: We observed a reduction of occipitotemporal areas’ (BA37) activation to unattended compared to attended faces and a modulation of primary visual areas’ activity lateralization. The latter was more right lateralized for attended than for unattended faces, and emotional faces were more right lateralized than neutral ones only in the former condition. Affective priming disappeared when emotional expressions of prime faces were ignored. Moreover, an increased activation in the right temporo-parietal junction (TPJ), but not in the intraparietal sulcus, was observed only for unattended angry facial expressions at approximately 170 ms after face presentation. Conclusions: We suggest that attentional resources affect the early processing in visual and occipito-temporal areas, irrespective of the faces’ threatening content. The disappearance of the affective priming effect suggests that when subjects were asked to focus on glasses’ shape, attentional resources were not available to process the facial emotional expression, even though emotion relevant and emotion irrelevant features of the face were presented in the same position. On the other hand, unattended angry faces evoked a pre-attentive TPJ activity, which most likely represents a bottom-up trigger that signals their high behavioral relevance, although it is unrelated to task demands.